2022
DOI: 10.3390/ijerph19073993
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Voices in Physical Activity Research: A Qualitative Review and Synthesis of UK Children’s Perspectives

Abstract: Background: Physical activity during childhood is associated with multiple short- and long-term health benefits. Physical activity levels decline throughout primary school emphasising a need for effective strategies to promote more activity in children. Children have rarely been involved in the intervention development process. This gap is an important omission and there is much to be learnt from existing qualitative studies with children, which could serve as a starting point for specific projects. This syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 67 publications
0
17
0
4
Order By: Relevance
“…Factors in the school environment (microsystem), such as peers and teacher-pupil relationships, were found to impact pupils' involvement in school-based PA. Positive and supportive environments encouraged participation and have been highlighted in previous reviews (16,25,26). Lubans et al (26) claimed that supportive environments are shaped by the language, behavior, and expectations of both pupils and teachers and that nurturing students' psychological needs including their sense of relatedness, competence, and autonomy are critical to establishing supportive PA environments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Factors in the school environment (microsystem), such as peers and teacher-pupil relationships, were found to impact pupils' involvement in school-based PA. Positive and supportive environments encouraged participation and have been highlighted in previous reviews (16,25,26). Lubans et al (26) claimed that supportive environments are shaped by the language, behavior, and expectations of both pupils and teachers and that nurturing students' psychological needs including their sense of relatedness, competence, and autonomy are critical to establishing supportive PA environments.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important finding because whether children understand the benefits of PA is disputed (64). In their review, Emm-Collison et al (25) indicated that children are aware of the benefits of PA due to cultural shifts and the increased exposure of children to mass media campaigns focusing on health and PA promotion (19). This illustrates the impact of the macrosystem (social and cultural attitudes and ideologies) on pupil participation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriate outdoor and indoor space, access to equipment, and parental support have been identified as facilitators of physical activity during the pandemic and related restrictions [ 24 27 ], a finding echoed in a number of quantitative studies [ 13 ]. It is important to note that parental influences [ 29 , 30 ] and access to facilities [ 30 , 31 ] have been shown to influence physical activity behaviour among children prior to the COVID-19 pandemic. However, findings within the current study are suggestive of an increased importance during times of severe COVID-19 restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of social influences in physical among children has been well documented in pre-pandemic research [ 30 , 32 , 33 ]. Loss of social connections among children during periods of lockdown and isolation and its impact on wellbeing and physical activity has emerged in recent qualitative research [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%